Aplikasi Sistem Informasi Geografis untuk Pemetaan Kerapatan Vegetasi dan Penutup Lahan Hubungannya dengan Daerah Resapan Air di Kawasan Pariwisata Ubud, Gianyar, Bali - Tiurmauli, Isabella; Trigunasih, Ni Made; Bhayunagiri, Ida Bagus Putu (Nandur, 2023)
In urban environments, the land cover composition plays a crucial role in determining the hydrological processes, particularly the infiltration rate. The Normalized Difference Vegetation Index (NDVI) is widely used to assess vegetation abundance and health. This discussion paper aims to investigate the relationship between land cover types and NDVI values in the context of infiltration in urban areas. Ubud District is one of the urban and tourism areas with a population and tourism that continues to increase resulting in the conversion of land functions into residential areas, highways, and industrial development. This research employed a descriptive qualitative method, with data analysis techniques utilizing digital classification and spectral index transformation on Sentinel 2A remote sensing data from the year 2022. The results of the study revealed that areas with forest and vegetation cover, characterized by high vegetation density (values ranging from 0.59 to 0.95), contribute to favorable infiltration conditions in urban and tourism areas.Vegetation cover, as indicated by higher NDVI values, positively influences infiltration rates by improving soil structure and water absorption. Incorporating green spaces and vegetation into urban planning strategies can help mitigate stormwater runoff issues and promote sustainable stormwater management practices. However, further research is needed to comprehensively understand the complexities associated with the relationship between land cover, NDVI, and infiltration under various urban contexts.